Relapse episodes in childhood primary nephrotic syndrome treated by alternate or three consecutive daily dose prednisone therapy - Denny Sujatno; M. P. Damanik; Purnomo Suryantoro (Indonesian Pediatric Society Publishing House, 2016)
Background Prednison is still the drug of choice for the treatment of nephrotic syndrome, especially for those with minimal change. Methods of treatment to optimize the effectiveness and efficacy are still in discussion. Objectives To evaluate the episode of relapsing minimal change nephrotic syndrome patients who received prednisone therapy by alternate or by three consecutive dose methods. Methods We performed a retrospective cohort study using medical records of the patients with primary nephrotic syndrome admitted to Division of Nephrology, Sardjito Hospital, Yogyakarta from January 1995 to January 2005. Subjects were divided into two groups, the first group treated with alternate days while the second group with three consecutive days prednisone program. Evaluation had been done to compare both treatment program (alternate days or consecutive days). Results Relapse episodes after six month recovery periods with alternate days treatment was 33% while those with consecutive days was as high as 83% (P>O.Ol). Conclusion Alternate dose group has a lower relapse event compared to three consecutive dose group in children with nephrotic syndrome.